2011
DOI: 10.4103/0975-3583.78597
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of left ventricular mass in normotensive type 2 diabetes mellitus patients with that in the nondiabetic population

Abstract: Cardiovascular disease is increased in individuals with type 1 or type 2 diabetes mellitus (DM). Left ventricular hypertrophy (LVH), which is an ominous prognostic sign and an independent risk factor for cardiac events, is often present in type 2 DM patients. The aim of our cross-sectional study was to evaluate the prevalence of LVH, and risk factors for its development, in normotensive type 2 diabetic patients without antihypertensive medication. The objectives of the study were to find out the prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 13 publications
4
23
2
2
Order By: Relevance
“…LVH is heavily overrepresented in patients with diabetes [19,23] and the existence of a specific diabetic cardiomyopathy has been an ongoing debate over the past decades [24]. It is likely to presume that the “harmful” diabetic phenotype overrides the cardioprotective and/or the blood pressure lowering effects of the minor allele of rs5068 .…”
Section: Discussionmentioning
confidence: 99%
“…LVH is heavily overrepresented in patients with diabetes [19,23] and the existence of a specific diabetic cardiomyopathy has been an ongoing debate over the past decades [24]. It is likely to presume that the “harmful” diabetic phenotype overrides the cardioprotective and/or the blood pressure lowering effects of the minor allele of rs5068 .…”
Section: Discussionmentioning
confidence: 99%
“…Santra et al in 135 normotensive individuals, half with DM and half healthy, reported higher LV mass in DM patients compared to controls [20]. In the Framingham Heart Study, increased LV mass and wall thickness was independently associated with DM, although in multivariable analysis, significance was reached only in females [21].…”
Section: Discussionmentioning
confidence: 99%
“…En la literatura biomédica existen escasos estudios sobre HVI en pacientes diabéticos en ausencia de HTA (12) . En el trabajo de Dawson et al (3) el 61% de diabéticos tuvieron HTA y en el estudio de Framingham (13) se encontró HVI en el 28% de mujeres sobre los 60 años con presiones arteriales sistólicas mayores de 125-139 mmHg.…”
Section: Discussionunclassified
“…Por ello cobran especial interés las investigaciones que tienen como objetivo estudiar la relación existente entre la HVI y la DM en ausencia de otros factores cardiovasculares; en este trabajo se encontró una frecuencia de 63,7% de HVI en pacientes diabéticos sin antecedentes de causas definidas para esta enfermedad; valor que coincide con otros estudios que informan porcentajes similares en diferentes poblaciones (12,13,15) ; lo cual refuerza la hipótesis planteada. Esta investigación sugiere, además, que los adultos mayores del sexo femenino que padecen de DM son el grupo de riesgo más vulnerable a desarrollar HVI, tal como lo sugieren otros estudios (16,17) .…”
Section: Discussionunclassified